(untitled) (Papeles, 2024)
Introduction: The teachers’ learning beliefs and conceptions define the two types of the activities they carry out with their students: student-centered or teacher-centered. Novice teachers have a teacher-centered approach, so teacher education programs can promote the change towards a student-approach. However, there are just a few studies that document this change, particularly with high school teachers in the area of natural sciences. Do teaching beliefs change throughout the pre-service teachers education program? Methodology: A qualitative study was carried out using the instrument Drawing of a Science Teacher, to document the evolution of beliefs about teaching that teachers enrolled in a teacher training program have. Results and discussion: This research shows that after taking courses in the psychopedagogical and teaching practice area, the majority of teachers change their focus from teacher-centered teaching to student-centeredness. Conclusion: Teacher training programs are essential to enhance teaching skills to reflect on the design of their teaching and their most frequent strategies. It is important to highlight that, although many student teachers initially adopt an egocentric approach, after teacher training a change is experienced due to a student-centered orientation.